Research on Effect of Ship Speed on Unsteady Hydrodynamic Performance of Bow Thrusters in Berthing and Departure Directions - He Cai; Xiaoqian Ma; Tan Wen; Yu Sun; Zhiyuan Yang; Yilong Tan; Jianyu Zhuo (Journal of Marine Science and Engineering)
With the continuous development of the shipping market, bow thrusters have become more important for ship maneuvering. Therefore, the performance of bow thrusters is studied in this paper. In order to obtain an unsteady performance of the bow thruster under different ship speed conditions, the SST k-ω turbulence model is adopted to predict the hydrodynamics of the bow thruster. With the ship’s speed increasing gradually, the variation characteristics of hydrodynamic coefficients and the flow field distribution at key positions are analyzed. The results show that with an increase in ship speed to three knots, the thrust coefficient and torque coefficient of the bow thruster decrease by 2.69~4.07% and 2.34~3.08%. In addition, the blade vibration amplitude intensifies. In the departure direction, the propeller load is more susceptible to being influenced and decreases by an additional 2.34~4.16% compared with that in the berthing direction. Meanwhile, it is found that the velocity distribution is asymmetrical. The inlet velocity at the bow side is faster, which results in the maximum peak pressure being about three times the minimum peak pressure. In addition, the pressure’s nonuniformity in the tunnel increases gradually with the increase in ship speed. Compared with the pressure distribution in the berthing direction, the pressure distribution before and after the propeller is more uniform, which is consistent with the results of hydrodynamic change and velocity distribution. The research in this paper has a certain reference significance for understanding the hydrodynamic performance of bow thrust operation.